A comparison of Glossina morsitans centralis originating from Tanzania and Zambia, with respect to vectorial competence for pathogenic Trypanosoma species, genetic variation and inter-colony fertility - Moloo, S.K.; Gooding, R.H. (Wiley, 1995)
Two laboratory strains of G. morsitans centralis originating from different fly-belts (one from Singida, in Tanzania, and the other from Mumbwa, in Zambia) were compared with respect to vectorial competence for pathogenic Trypanosoma species, genetic variation and inter-colony fertility. The vectorial competence of G. m. centralis of Tanzanian origin for T. vivax and T. congolense is similar to, whereas for T. brucei brucei it is lower than the colony of Zambian origin. Nevertheless, these 2 laboratory strains of G. m. centralis showed levels of susceptibility to the 3 pathogenic Trypanosoma species which were much greater than previously observed in laboratory colonies of other Glossina species. Electrophoresis of 15 enzymes revealed that the 2 colonies differ significantly in allele frequencies at only 3 loci that are relatively close together on one of the autosomes. Hybridization experiments revealed that G. m. centralis from the 2 fly-belts are consubspecific.